Does induction of labour increase the risk of caesarean section? A systematic review and meta‐analysis of trials in women with intact membranes. (3rd July 2013) - Wood, S; Cooper, S; Ross, S
<x xml:space="preserve">Abstract</x> Background Recent literature on the effect of induction of labour (compared with expectant management) has provided conflicting results. Reviews of observational studies generally report an increase in the rate of caesarean section, whereas reviews of post‐dates and term prelabour rupture of membrane (PROM trials suggest either no difference or a reduction in risk. Objective To evaluate with a systematic review and meta‐analysis of randomised controlled trials (RCTs) whether or not the induction of labour increases the risk of caesarean section in women with intact membranes. Search strategy Literature search using electronic databases: MEDLINE, EMBASE, and the Cochrane Database of Clinical Trials. Selection criteria RCTs comparing a policy of induction of labour with expectant management in women with intact membranes. Data collection and analysis A total of 37 trials were identified and reviewed. Quantitative analyses with fixed‐ and random‐effects models were performed with revman 5.1. Main results Of the 37 RCTs, 27 were trials of uncomplicated pregnancies at 37–42 weeks of gestation. The remaining ten evaluated induction versus expectant management in pregnancies with suspected macrosomia (two), diabetes in pregnancy (one), oligohydramnios (one), twins (two), intrauterine growth restriction (IUGR) (two), mild pregnancy‐induced hypertension (PIH) (one), and women with a high‐risk score for caesarean section (one). Meta‐analysis of 31 trials determined that a policy of induction was associated with a reduction in the risk of caesarean section compared with expectant management (OR 0.83, 95% CI 0.76–0.92). Author's Conclusions Induction of labour in women with intact membranes reduces the risk of caesarean section. Review of the trials suggests that this effect may arise from non‐treatment effects, and that additional trials are needed.